Fiscal efficiency of excise duty on passenger cars in Poland - Sygut, Edyta (Wydajność fiskalna podatku akcyzowego od samochodów osobowych w Polsce, 2019)
Excise duty is a harmonised tax within the EU; however, EU law does not govern the imposition of excise duty on passenger cars. EU Member States were granted the right to tax non-harmonised products or services and the freedom to shape such regulations. The purpose of this article is to state the reasons why excise duty is imposed on passenger cars, as well as to analyse and assess the fiscal efficiency of the imposition of excise duty on passenger cars in Poland. The analysis covered the budget revenue from excise duty on passenger cars in 2009-2017. The conclusion is that the reason of the imposition of excise duty on passenger cars in Poland is mainly the implementation of the fiscal function. The excise duty revenue on passenger cars is a stable source of budget revenue; however, its importance in the total excise duty revenue structure is only supplementary. The revenue related to the Intra-Community acquisition of passenger cars to Poland has a dominant share in this structure
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 78-89
Keywords: excise duty; passenger car; luxury goods; environmental tax; fiscal efficiency; podatek akcyzowy; samochód osobowy; dobra luksusowe; podatek ekologiczny; wydajność fiskalna